The differences between two-part sentences in Chinese and Kazakh languages (Journal of Oriental Studies, 2018)
In this article we comprehensively conducted the differences betweentwo-part sentences in Chinese and Kazakh languages. Chinese is SVO form- language, in chinese the verb is formed by peculiarities of forming verbalsentences. The are not any big morphological changes. In any case: «peculiarityremains + verb is the basis + result remains». In sentences thesubject, the object and adverbial modifier are placed before the predicate.The word - combination and word formation are formed by this way. Aslong as the auxiliary word and prepositions form the member of the sentence.Therefore, the words tend to change places, members of the sentenceare widely used. However, in both languages the role of the subjectand predicate remains unchanged.